2021
DOI: 10.3390/molecules26113479
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Fibers Decorated with MnO2 for Wire-Shaped Supercapacitor

Abstract: Fibers made from CNTs (CNT fibers) have the potential to form high-strength, lightweight materials with superior electrical conductivity. CNT fibers have attracted great attention in relation to various applications, in particular as conductive electrodes in energy applications, such as capacitors, lithium-ion batteries, and solar cells. Among these, wire-shaped supercapacitors demonstrate various advantages for use in lightweight and wearable electronics. However, making electrodes with uniform structures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 66 publications
1
6
1
Order By: Relevance
“…6d demonstrate that the combination of the three devices in series increases the operating voltage with similar charge/discharge time for a same load, hence increasing the specific energy and power required for practical applications. For instance, the series connection of the devices results in an energy density of 52 nWh for a power density of 90 µW, which compares well with other similar solid-state EDLC-based supercapacitors reported in the literature [49], [50], [51]. It is true that the use of a pseudocapacitive material or doping agent would allow to achieve higher energy densities, but it could also result in an inferior rate performance and cycling life [52].…”
Section: Micro-supercapacitor Design and Characterizationsupporting
confidence: 77%
“…6d demonstrate that the combination of the three devices in series increases the operating voltage with similar charge/discharge time for a same load, hence increasing the specific energy and power required for practical applications. For instance, the series connection of the devices results in an energy density of 52 nWh for a power density of 90 µW, which compares well with other similar solid-state EDLC-based supercapacitors reported in the literature [49], [50], [51]. It is true that the use of a pseudocapacitive material or doping agent would allow to achieve higher energy densities, but it could also result in an inferior rate performance and cycling life [52].…”
Section: Micro-supercapacitor Design and Characterizationsupporting
confidence: 77%
“…Figure g shows a comparison of the specific capacitance of the supercapacitor in this study and recently reported FSSCs based on carbon-based fiber electrodes. The specific capacitance reported in this work is larger than many previously reported FSSCs, including supercapacitors based on ACF (54.2 at 0.2 A g –1 ), MnO 2 /CNTF (17.1 at 1 A g –1 ), Mn 3 O 4 and MoS 2 /CF (70 at 0.5 A g –1 ), NCHrGO/CF//NQrGO/CF (69.1 at 0.41 A g –1 ), MWCNT/MOF (151.1 at 1 A g –1 ), CF/CNT/MnO 2 //CF/CNT/PPy (59.7 at 0.5 A g –1 ), and FHRCF (122.2 at 1 A g –1 ) …”
Section: Resultscontrasting
confidence: 53%
“…Calculated from GCD curves, the specific capacitance and energy density of the supercapacitor were 43 F g À1 and 3822 mwh kg À1 at current density of 0.1 A g À1 , respectively, which were comparable with other MnO 2 / CNTs-based supercapacitor with using homogeneous polymer electrolyte. [39][40][41] The specific capacitance of supercapacitor devices could be further enhanced by using polyelectrolytes with ionic liquid solvent or other electrode materials with high pseudocapacitance. The BHP-based supercapacitor with using MnO 2 /CNTs composite electrodes exhibited a capacitance retention of 60.5% as the discharge current density increased from 0.1 to 1.0 A g À1 (Figure S9, Supporting Information), indicating good rate performance.…”
Section: Resultsmentioning
confidence: 99%